Dissolution Kinetics of Milled-Silicate Rock Fertilizers in Organic Acid - Priyono, Joko; Gilkes, Robert John (UNIVERSITY OF LAMPUNG, 2008)
A dissolution experiment was carried out to identify the effects of milling condition on dissolution kinetics of silicate rock fertilizers. Initially ground materials (Ø < 250 μm for basalt, dolerite, gneiss, and Ø < 150 μm for K-feldspar) were further milled with a ball mill (Spex 8000) under dry and wet conditions for 10, 60, and 120 minutes. The rock powders were dissolved in a mixture of 0.01M acetic-citric acid at a rock powder/solvent ratio of 1/1000, and the solution was agitated continuously on a rotary shaker at 25o C. The concentrations of dissolved Na, K, Ca, Mg, Al, and Si from the milled rocks were determined at intervals from 1 hour up to 56 days. Results indicated that the relationships of quantity of dissolved rock and elemental plant nutrients (Et) with time (t) were well described by a power equation: Et = Eo + atn with reaction order (n) of 0.3 – 0.8. Milling increased quantity of total and individual dissolved element (Et ), dissolution rate (Rt), the proportion of rapidly soluble rock or element (Eo), and dissolution constant a. The increases in dissolution due to dry milling were larger than for wet milling. Although further proves should be provided, results of this dissolution experiment clearly indicates that SRFs may be used as multinutrient fertilizers as well as remedial materials for acidic soils; and dry milling may be applied as an appropriate method for manufacturing effective SRFs.